PROSTHETIC IMPLICATIONS OF DENTAL ANOMALIES - M., Rithanya; Kommi, Venkatesh; Sashank, Keerthi; M.P., Brundha (International Journal of Psychosocial Rehabilitation, 2020)
This paper is aimed at describing a number of dental anomalies that every dental practitioner of all disciplines will be destined to encounter. The dental anomalies, how they affect the particular prosthetic implications, and what could be done for treatment if alterations could be done in the prosthetic implications are discussed in this review article. A number of articles, around 40, were collected from search engines like PubMed , Scholar, and so much more. The articles were thoroughly reviewed to write this article on dental anomalies affecting prosthetic implications. Dental anomalies are the abnormalities present in the teeth and oral cavity. Dental anomalies are a wide range of disorders comprising various disorders of the teeth in the categories of acquired abnormalities and developmental abnormalities. Developmental anomalies are divided into five groups for classification. They are abnormalities in size, number, morphology, shape, and the location of the tooth. The teeth number anomalies are hypodontia and hyperdontia. In these abnormalities there will be a lower number of teeth and an increased number of teeth, respectively. We also have positional anomalies, which include transposition. Morphological anomalies include concrescence, fusion, and gemination (double teeth). The other abnormalities are taurodontism, dilaceration including supernumerary roots, dens evaginatus, and dens invaginatus. Structural anomalies include dentinogenesis imperfecta and amelogenesis imperfecta. Tooth impaction is also one of the developmental anomalies seen. Acquired tooth disorders include tooth ankylosis and resorption. Hypercementosis, pulp stone, tooth fluorosis, abrasion, erosion, syphilitic hypoplasia, and molar incisor hypo mineralization are some of the other acquired dental anomalies.